Pengaruh Earnings Per Share, Arus Kas Operasi, Ukuran Perusahaan Terhadap Harga Saham - Riska Damayanti; Prima Sadewa (eCo-Fin, 2023)
The purposes of this study are (1) to determine the effect of earnings per share, operating cash flow and company size together on stock prices, (2) to determine the effect of earnings per share on stock prices, (3) to determine the effect of cash flows operations on stock prices, (4) To determine the effect of company size on stock prices. This research is research that uses a quantitative approach. Furthermore, this research is a type of associative research. The data collection technique is a purposive sampling method. Methods of data analysis in this study are descriptive statistical tests, research model tests, classical assumption tests, regression tests and hypothesis testing. The results in this study are as follows: (1) there is an effect of earnings per share, operating cash flow, and company size together on stock prices (2) there is an effect of earning per share on stock prices, (3) there is an effect of operating cash flow on stock prices, (4) there is an effect of company size on stock prices.